Grazing practices affect the soil microbial community composition in a Tibetan alpine meadow. (13th November 2018) - Yang, Fei; Niu, Kechang; Collins, Courtney G.; Yan, Xuebin; Ji, Yangguang; Ling, Ning; Zhou, Xianhui; Du, Guozhen; Guo, Hui; Hu, Shuijin
Abstract: Grazing is the primary land‐use activity on the Tibetan Plateau and can affect soil microbes and their function through aboveground vegetation removal, animal trampling, and manure deposition. Two distinct grazing systems (i.e., winter grazing [WG] and annual grazing [AG]) dominate on the Tibetan Plateau, but their effects on soil microbes have rarely been assessed. Taking advantage of a 5‐year field experiment that controlled timing and density of grazers via fence exclosures, we examined impacts of different grazing practices on the biomass, diversity, and composition of the soil microbial community in a Tibetan alpine meadow. On the basis of high‐throughput sequencing, we found that grazing had no significant effects on bacterial and fungal α‐diversities but altered their community compositions. Although total soil carbon (TC), total soil nitrogen (TN), and carbon/nitrogen (C/N) were related to both bacterial and fungal community compositions, plant shoot biomass only correlated with bacteria, and soil pH and moisture significantly influenced fungi under grazing. Also, grazing altered plant community composition but did not lead to corresponding changes in bacterial or fungal community composition. Moreover, grazing practices affected the relative abundance of specific bacterial and fungal taxa, reducing Actinobacteria but increasing Basidiomycete fungi in WG. Soil TC and TN were higher, and the soil microbial community was more stable in AG than WG, likely due to more stable litter inputs in AG. Together, these results showed that AG was less disruptive to soil microbes, suggesting that AG may provide a viable option for sustainable utilization and conservation of these fragile alpine systems.